The THES university rankings: are they really world class? / Richard Holmes - Holmes, Richard (ACRULeT, Faculty of Education & UiTM Press, 2006)
The Times Higher Education Supplement (THES) international ranking of universities, published in 2004 and 2005, has received a great deal of attention throughout the world, nowhere more so than in East and Southeast Asia. This paper looks at the rankings and concludes that they are deficient in several respects. The sampling procedure is not explained and is very probably seriously biased, the weighting of the various components is not justified, inappropriate measures of teaching quality are used, the assessment of research achievement is biased against the humanities and social sciences, the classification of institutions is inconsistent, there are striking and implausible changes in the rankings between 2004 and 2005 and they are based in one crucial respect on regional rather than international comparisons. It is recommended that these rankings should not be the basis for the development and assessment of national and institutional policies.